Antioxidant and anti-aging effects of Warburgia salutaris bark aqueous extract: evidences from in silico, in vitro and in vivo studies - Abdel-Fattah, Mohamed; Dmirieh, Malak; Ben Bakrim, Widad; Mouhtady, Omar; Ghareeb, Mosad A.; Wink, Michael; Sobeh, Mansour (Journal of ethnopharmacology, 2022)
Ethnopharmacological relevance - The genus Warburgia (family Canellaceae) is widely distributed over Afrotropical and Neotropical realms. Traditionally, W. salutaris (G. Bertol.) Chiov., and other Warburgia species are used as anti-inflammatory, antimalarial, antimicrobial, and for wound healing, and treating several skin complaints as well. Specifically, different extracts from W. salutaris were reported to possess diuretic, anti-inflammatory, and cytotoxic effects. - Aim of the study - This work aimed to investigate the phytochemical composition of an aqueous extract from W. salutaris bark, and evaluate its antioxidant and anti-aging activities in silico, in vitro, and in vivo. - Materials and methods - HPLC-PDA-MS/MS was used to investigate the phytochemical components of the extract. The antioxidant potential of the extract was evaluated in vitro using DPPH and FRAP assays. The Caenorhabditis elegans nematodes model was adopted to investigate the antioxidant and the anti-aging effects in vivo by determining the worms' survival rate, level of ROS, HSP16 expression, and nuclear translocation of the transcription factor DAF16. Molecular operating environment (MOE) software was utilized for in silico molecular docking of the extract's components into different enzymes involved in the aging process. Anti-collagenase, anti-elastase, anti-tyrosinase, and anti-hyaluronidase assays were used to evaluate the anti-aging effects in vitro. - Results - HPLC-MS analysis furnished 30 compounds, among them catechin, 11α-hydroxy muzigadiolide, mukaadial, pereniporin B, and 11α-hydroxycinnamosmolide. The major components of the extract showed appropriate fitting in the binding site of the target enzymes adopted in the study with considerable minimum free binding energy relative to the standard inhibitors. The extract showed substantial in vitro antioxidant activity in DPPH and FRAP assays and in vitro anti-aging assays against collagenase, elastase, tyrosinase, and hyaluronidase with comparable IC50 values to the reference standards. Moreover, it attenuated oxidative stress in vivo as it significantly increased the survival rate of ROS stressed C. elegans worms, decreased intracellular ROS, decreased the juglone-induced HSP16 expression and enhanced the nuclear localization of DAF16 in a dose-dependent manner. - Conclusion - Our results support the traditional use of W. salutaris to counteract inflammation and oxidative stress associated with several pathological conditions. In addition, W. salutaris bark extract can be considered as a substantial source for bioactive metabolites with strong potential as anti-aging and antioxidant agents.